Stimulation of Hemolysis and Eryptosis by β-Caryophyllene Oxide - Sumiah A. Alghareeb; Mohammad A. Alfhili; Jawaher Alsughayyir (Life, 2023)
Background: Eryptosis stimulated by anticancer drugs can lead to anemia in patients. β-caryophyllene oxide (CPO) is an anticancer sesquiterpene present in various plants; however, its effect on the structure and function of human red blood cells (RBCs) remains unexplored. The aim of this study was to investigate the hemolytic and eryptotic activities and underlying molecular mechanisms of CPO in human RBCs. Methods: Cells were treated with 10–100 μM of CPO for 24 h at 37 °C, and hemolysis, LDH, AST, and AChE activities were photometrically assayed. Flow cytometry was employed to determine changes in cell volume from FSC, phosphatidylserine (PS) externalization by annexin-V-FITC, intracellular calcium by Fluo4/AM, and oxidative stress by 2′,7′-dichlorodihydrofluorescein diacetate (H2DCFDA). Cells were also cotreated with CPO and specific signaling inhibitors and antihemolytic agents. Furthermore, whole blood was exposed to CPO to assess its toxicity to other peripheral blood cells. Results: CPO induced concentration-responsive hemolysis with LDH and AST leakage, in addition to PS exposure, cell shrinkage, Ca2+ accumulation, oxidative stress, and reduced AChE activity. The toxicity of CPO was ameliorated by D4476, staurosporin, and necrosulfonamide. ATP and PEG 8000 protected the cells from hemolysis, while urea and isotonic sucrose had opposite effects. Conclusions: CPO stimulates hemolysis and eryptosis through energy depletion, Ca2+ buildup, oxidative stress, and the signaling mediators casein kinase 1α, protein kinase C, and mixed lineage kinase domain-like pseudokinase. Development of CPO as an anticancer therapeutic must be approached with prudence to mitigate adverse effects on RBCs using eryptosis inhibitors, Ca2+ channel blockers, and antioxidants.